Propriedades elétricas e térmicas em materiais bidimensionais - Sá, Louis Gustavo da Costa Sobral e (2022)
With the synthesis of graphene in the laboratory and advances in research into new two-dimensional materials, the control of electrical and thermal conduction is essential for the development of new technologies. Thus, we investigated the electrical properties such as conductance and the effects of spin-orbit interaction in topological insulators and the effects of the presence of defects, such as the grains that are produced in the growths of polycrystalline samples, on the thermal conductivity, which are of crucial importance in the construction and enhancement of new devices. For this purpose, this thesis was divided into two parts. In the first one, we investigate the electrical transport in quasi-one-dimensional graphene nanoribbons that have a crystal lattice described by two overlapping triangular lattices, and therefore it has what we call sublattice symmetry that is related to the chirality sign that is studied in the random matrix theory ensembles. For this, we used the tight binding method to analyze graphene from three Hamiltonian models and measure the electrical conductance in different scenarios, as a function of energy, disorder force and magnetic flux. Consequently, it was possible to demonstrate that all models present the chirality sign, which is a result of great importance in the study of strongly correlated systems. Furthermore, through the maximum entropy principle we measure the correlation length via peak density, that is, we only count the number of conductance maxima in a given range of magnetic flux, confirming that such relevant quantity in the experimental area can be determined through a single realization. In the second part of the thesis, we explore the thermal properties of pristine and polycrystalline silicene. The systems were modeled using molecular dynamics and lattice dynamics to compute thermal conductivity, phonon state density and phonon dispersion relation. The results predict that the intrinsic thermal conductivity of 9.47 W/mK and an effective mean free path of 11.54 nm for the pristine silicene, however, as expected, in the polycrystalline samples the values of the thermal conductivities decrease as the effective grain sizes decrease or with increasing temperature. And the density of phonon states showed that low-frequency heat carriers are responsible for the change in thermal conductivity. In addition, the thesis contains the theoretical foundations of all the techniques used, as well as all the details to carry out the simulations.